(untitled) (Research, Society and Development, 2020)
Environmental education has a fundamental role to correct society’s aggression towards nature and the school, in this context, it is considered the key element to train the citizen who can change this course. In this research, the level of awareness of elementar school teachers in the municipality of Colares, in the state of Pará, is analyzed regarding the theoretical and practical repertoire in relation to environmental issues. The research was developed from primary data, collected from 78 public elementary school teachers in the municipality, which represents 75.72% of the number of teachers working at this level of education. Teachers are between 38 and 67 years old, 97.43% have higher education, and 92.31% are public servants. For teachers, the environment is in second place on a scale of values that must be worked on in the formation of citizens. However, it was found that there is a lack of training for teachers in the environmental area, which ends up interfering in the execution of activities and projects related to the theme. In the perception of teachers, within the school space, there is still a low appropriation of knowledge and practices aimed at environmental issues, since there are few green spaces and action projects for environmental education. The low adoption of educational practices inside and outside the school environment is worrying, demonstrating the need for na effective policy at the municipal level with the school as a link between environmental education and the community in general.